Vertebroplastia versus Cifoplastia en tratamiento de fracturas vertebrales osteoporóticas tipo of 1-3, en el Hospital Regional de Loreto. 2023 – 2024 - Blanco Payano, Richard Angel (2024)
The present project aims to evaluate two minimally invasive surgical treatments, vertebroplasty and kyphoplasty, in the treatment of type 1-3 osteoporotic vertebral fractures. The choice of these two interventions responds to the need to optimize medical care for patients in a unique geographic and demographic environment. The project aims to compare the clinical and radiological results and their complications of the treatment methods, vertebroplasty and kyphoplasty, in patients with osteoporotic vertebral fractures type OF 1-3, at the Regional Hospital of Loreto, in the years 2023 -2024. The study corresponds to an analytical type, prospective, cross sectional and comparative design. The sample corresponds to a minimum of 50 patients with a diagnosis of osteoporotic vertebral fracture type OF 1-3, divided into 2 groups, 25 who will receive treatment with percutaneous unipedicular kyphoplasty and 25 with percutaneous unipedicular vertebroplasty. 2 surveys will be used (demographic and functional with Oswestry index and numerical pain scale score) and 2 data collection forms (operative time, cement leak and volume, presence of adjacent fracture, regional kyphosis angle, height anterior, posterior and middle wall of the fractured vertebra and presence of fracture of adjacent vertebra). For the inferential analysis of quantitative variables, the Student t test for paired samples will be used to evaluate the changes of various parameters in both groups, and the Student t test for independent samples will be used to evaluate the difference between the two groups. For qualitative variables, the χ 2 test will be used for categorical data. In all analyses, a P value <0.05 will indicate that the difference will be statistically significant.